A professional register for probation practitioners in England and Wales: Opportunities and challenges - Tidmarsh, Matt (Probation journal, 2025)
Implemented in September 2024 against a backdrop of significant organisational challenges, the ‘Probation Professional Register’ aims to enhance confidence in the probation service in England and Wales, strengthen professional identity, and improve training and practice. It mandates, among other things, that probation officers evidence their qualifications; adhere to personal and professional standards of conduct; and commit to continuous professional development. Drawing on discussions from a one-day conference hosted at the University of Leeds in February 2024, this article examines the introduction of the professional register. In particular, it explores the opportunities and challenges associated with registration, situating these debates within the broader historical context of professionalism in probation. The article argues that, although registration was generally well received among conference participants, numerous and interlinked issues – inclusive of staffing shortages, high caseloads, inadequate pay, and perceptions of unnecessary bureaucracy – present significant obstacles to meaningful implementation. As such, the article concludes with some recommendations for how the register can be successful in driving (re)professionalisation rather than merely as a bureaucratic tool of regulatory compliance.